Análise da sustentabilidade da agricultura familiar participante do programa de aquisição de alimentos (PAA) no município de Toledo Paraná - Souza , Karine Daniele Byhain de (2016)
This research analyzes the Food Acquisition Programme (PAA) in Toledo city Paraná state in Brazil. Our aim is to observe whether the industry assurance, which was provided by the programme itself (PAA), takes into account its participants sustainability situation once we compare this situation to the family agriculture groups which are not part of it. Our general goal was to evaluate the PAA as a sustainability encouraging factor for family agriculture through its participants in the programme managed in Toledo city, in Paraná state, and to compare their situation with the family agriculture groups from the same area that are not part of the programme. In order to satisfy the research problem and meet the presented goals, the methodology applied consisted of qualitative and quantitative approaches. Our goals are described as descriptive research and its procedures as a survey. The data acquisition was carried out through a questionnaire with farmers and we also obtained data from secondary databases from the government itself. Through the questionnaire we interviewed 159 farmers who are part of the family agriculture and live in Toledo PR. After analyzing the data we confirmed that for the PAA participants their profit margins inside their farms are not related to more people working in it. For most farmers it is not difficult to enter and stay inside the programme. When comparing the obtained benefits from the PAA through farmers who are not part of the programme, in light of the sustainability, we confirmed that, generally, concerning these two groups, those who are part of the programme and those who are not, there are not considerable differences. As for the Sustainability Barometer we confirmed that both the programme participants and the non-participants fit the potentially sustainable scale range. The cost checking for the public sector while acting as an industry ensuring factor for agriculture family production confirmed that the costs for this sector are lower when compared to those achieved through bidding, once there are no subsidies. We concluded that there are not considerable differences between the sustainability conditions observed within the programme participants and non-participants in the Toledo PR area, once the farmers profiling and the Sustainability Barometer measurements are similar for both groups